2000
DOI: 10.1017/s1357729800054898
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for growth and carcass traits of Japanese Black (Wagyu) cattle

Abstract: Restricted maximum likelihood analyses fitting an animal model were conducted to estimate genetic parameters with a pooled-data set of performance tests (growth traits and food intake) on 661 bulls and progeny tests (growth traits and carcass traits) on 535 steers. Traits studied included concentrate intake (CONC), roughage intake (ROU), TDN conversion (TCNV), TDN intake (TINT) of bulls; rib eye area (REA), marbling score (MARB), dressing proportion (DRES) and subcutaneous fat depth (SCF) of steers. Body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
35
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 11 publications
35
35
10
Order By: Relevance
“…Other corroborated values as 0.22 by Hirooka et al (1996), 0.20±0·09 by Oikawa et al (2000) for Japanese Black steers and 0.20 by Hoque et al (2006) for Japanese Black young bulls supported the present results. Arthur et al (2001) concluded that the ADG to be moderately heritable (0.20) which was slightly less than the present observation.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 90%
See 1 more Smart Citation
“…Other corroborated values as 0.22 by Hirooka et al (1996), 0.20±0·09 by Oikawa et al (2000) for Japanese Black steers and 0.20 by Hoque et al (2006) for Japanese Black young bulls supported the present results. Arthur et al (2001) concluded that the ADG to be moderately heritable (0.20) which was slightly less than the present observation.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 90%
“…Akbulut et al (2002) estimated a corresponding heritability value of 0.29±0.148 for Brown Swiss calves. Oikawa et al (2000) estimated heritability (0·20 to 0·38) for growth traits, which were in between the range of present study (Table 5). Kemp et al (1988) and Tosh et al (1999) observed heritability of 0.19 and 0.15, respectively for BWT were lower than the present values.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 73%
“…Carcass weight and IMF were uncorrelated (0.00), even lower than that reported by Koots et al (1994b) for carcass weight and marbling score (0.15). The strongest genetic correlation for production traits was between the two measures of fatness: s.c. fat depth (P8) and IMF (0.36), which is higher than that reported in U.S. (Gregory et al, 1994), Japanese (Oikawa et al, 2000), and other Australian cattle (Reverter et al, 2000). The low correlation between these two measures of fatness indicates ample potential to select animals within breeds for improvements in both s.c. (not desirable) and i.m.…”
Section: Fat Distributionmentioning
confidence: 77%
“…In the current trial, when the leaner breeds (South Devon, Limousin, and Belgian Blue) were excluded from the analysis, the heritability for marbling was much higher (not reported). Others, such as Oikawa et al (2000), have reported high heritability estimates for marbling in highly marbled breeds (Wagyu). These differences highlight the importance of treating the current estimates as "pooled" across breeds rather than specific to any one breed.…”
Section: Fat Distributionmentioning
confidence: 99%
“…Comparisons between Wagyu cattle and other breeds regarding cell biology and general adipogenesis have been reported in several studies, such as those by Oikawa et al (2000), Hausman et al (2009), Dodson et al (2010a and Duarte et al (2013). Some studies comparing Wagyu cattle with other breeds (Hausman et al, 2009;Dodson et al, 2010a;Duarte et al, 2013) have emphasized the uniqueness of this breed and the importance of better understanding adipogenesis, mainly because its increased accumulation of fat within the skeletal muscle, which seems to not follow the same pattern of other adipose tissue depots.…”
Section: Introductionmentioning
confidence: 99%